EKSPANSI “TRUST” DALAM EVALUASI PENDIDIKAN MENITI KREADIBILITAS HASIL BELAJAR - Ali Akbarjono (Universitas Islam Negeri Fatmawati Sukarno, 2017)
Evaluation of Education is as a subsystem of implementing management of education that positionedas an educational institution having a centralistic position and becoming a media that accommodates the public assessment of the outcomes (output and outcome) achieved. Through the optimization of education evaluation evaluation has a positive impact on the cultivation of the values of public trust as one of the factors that contribute to the success of management of an educational institution because without buliding and actualizing trust well, the public only as a spectator who has apathy character of the effort of quality development both ranging from input quality, process and output. Ideally the implications of optimizing the implementation of the evaluation mechanism of education can be an instrument of the process of comparing the existing situation with certain criteria to the problems associated with academic in an educational institution because the evaluation of education is actually not only assessing the learning outcomes of students in a certain level of education, regarding the assessment of various aspects affecting the student’s learning process, such as evaluation of teachers, curriculum, methods, means of infrastructure, environment and so on. In general the scope of evaluation in the field of education in schools includes three main components namely: Evalua- tion of teaching programs, Evaluation of teaching implementation process, and Evaluation of learning outcomes. .